Optimization of Talc Pellets Preparation by Extrusion-Spheronization Technique: A 3² Factorial Design Approach - Ranjeet Jadhav (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: This study aims to optimize talc pellet preparation using the extrusion-spheronization technique through a 3² factorial design approach. By varying binder concentration and spheronization time at three levels each, we assessed their impact on pellet characteristics, including size, shape, density, and friability. The results indicate that both factors significantly influence pellet quality, with higher binder concentrations and longer spheronization times producing more uniform and spherical pellets. This research provides a robust methodology for optimizing palletisation processes in pharmaceutical applications. Talc, a hydrous magnesium silicate, is widely used in the pharmaceutical industry for its properties as a glidant, lubricant, and diluent. The extrusion-spheronization technique is popular for producing spherical pellets with uniform size and density, crucial for consistent drug delivery. This study aims to optimize talc pellet preparation using a 3² factorial design approach by investigating the effects of binder concentration and spheronization time on pellet characteristics and determining the optimal conditions for high-quality pellet production. Results: Higher binder concentrations and longer spheronization times resulted in more uniform and spherical pellets with higher density and lower friability. ANOVA indicated that both variables significantly affected pellet characteristics, with significant interactions between them. Response surface plots highlighted optimal conditions for each response variable, confirming the critical role of binder concentration and spheronization time in the extrusion-spheronization process. Conclusion: The study successfully optimized talc pellet preparation using the extrusion-spheronization technique through a 3² factorial design. Higher binder concentrations and longer spheronization times produced high-quality pellets, providing a robust framework for process optimization in pharmaceutical manufacturing.